EMPIRICAL EVIDENCE OF CROWDFUNDING STUDIES IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Widya Ningsih; Doddy Setiawan; Y Anni Aryani (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to collect and analyze related scientific literature to provide empirical evidence on the development of crowdfunding studies in Indonesia. This study analyzed forty-four crowdfunding articles derived from Scopus and Sinta 2. We classified the articles based on the frequency of publication per year, research methods, theoretical focus, and themes used in studies on crowdfunding in Indonesia. This study found that the most articles were published in 2020 and 2023, with qualitative research methods being the most frequently used. The general theoretical foundation does not yet exist, but more and more articles discuss legal theory, and the most frequently researched themes are crowdfunding analysis and factors that analyze investor behavior, funding speed, and psychological or technological factors that affect user intention to use crowdfunding platforms. Finally, this review can contribute to the development of theoretical and empirical research on new crowdfunding issues in Indonesia by serving as an academic foundation.